Evaluation of reinforced and green bioplastic from carrageenan seaweed with nanocellulose - Fatmawati, Adam; Nor Amira, Othman; Nur Hidayah, Mat Yasin; Cheng, Chin Kui; Nurul Aini, Mohd Azman (The Korean Fiber Society, 2022)
In this work, bioplastic was formulated through the incorporation of cellulose into refined carrageenan. Three different sizes of cellulose were used microcrystalline cellulose (MCC), cellulose nanowhisker (CNW) and nanofibrillated cellulose (NFC). The CNW was mechanically nano-grinded and NFC was ultrasonicated to produce nano particle for MCC. The CNW has the smallest particle size distribution and an average size of 54 nm. The abundance of hydroxyl groups in the cellulose structure forms intermolecular interactions with the carrageenan and increases the viscosity (293.90 mPas), shear stress (27.90 Pa) and tensile strength (19.87 MPa) of Carra-CNW bioplastic. This revealed increasing intensity and a shift of 1H-NMR due to hydrogen becoming closer to an electronegative atom in both micro and nano size cellulose. At a larger cellulose size, Carra-MCC is thermally stable and the activation energy (Ea) is 73.81 kJ/mol higher than Carra-CNW Ea at 47.14 kJ/mol. Cellulose incorporated into a carrageenan matrix is a potential eco-material that could replace conventional plastic where the sample decomposes up to 65 % of the initial weight in biodegradability and compostability test. The water vapour permeability value is in the range of 3.43 to 4.09×10−14 g s−1 m−1 Pa−1. In conclusion, carrageenan incorporated with cellulose potentially suitable for uses such as food packaging applications based on the results of the mechanical strength, thermal stability and decomposition tests conducted.